Optimization of Standalone Solar Heat Fired Absorption Chiller for Typical Australian Homes. (June 2016) - Abdullah, Gazinga F.; Saman, Wasim; Whaley, David; Belusko, Martin
Abstract: The increased penetration of residential air-conditioners (AC); specifically vapor compression types, is regarded as one of the foremost causes of a dramatic rise in critical peak electricity demands requiring corresponding upgrades of electricity infrastructures. These upgrades requires heavy investments, consequently, driving up electricity prices. Solar air-conditioning systems can reduce this trend, but current vapor-compression air-conditioners (VCACs) needs very large investments in both photovoltaic system and battery storage. Alternatively solar heat-driven absorption chillers need less expensive solar collectors and thermal storage, drawing only small amounts of electricity to overcome parasitic power. There are ample studies conducted previously on either the technical and/or economic feasibility of solar heat driven absorption chillers. But these studies are only focused on supplementing solar heat energy with an auxiliary heater. This study, examines the option of running the absorption chiller by solely relying on solar heat energy. It focuses on minimizing the life cycle cost of a solar heat driven absorption chiller through optimizing the size of all of its main components. The system is named the standalone solar heat fired absorption chiller (SA-SHF-ABS-CH) sized to sufficiently meet the space conditioning demands, both heating and cooling, of a typical Australian 6 star home. For the aims of this research, TRNSYS17 software was used in modelling and dynamically simulating the integrated system, while GenOpt software was used to carry out the optimization. The economic assessment on the most optimally sized system component configuration shows, firstly, the twenty-year lifecycle cost of the system with the most minimized cost is AU 53, 387 in Brisbane, AU 51, 639 in Adelaide and AU 32, 816 in Melbourne. These investment costs in each of these cities appear higher than those incurred if the householder were to instead install a standard efficient inverter, ducted, reverse cycle air conditioner (IRC-AA-HP) powered by grid electricity; as follows: Brisbane at 77%, Adelaide at 58% and Melbourne at 28%. Secondly, the payback period was found to be longer than the twenty-year system service- life, which is far too long to justify the investment on such solar air-conditioner. However, when compared with IRC-AA-HP, in Adelaide and Melbourne, SA-SHF-ABS-CH consumed at least 50% less power, meaning it offsets half of the carbon dioxide emissions, furthermore, it draws 75% lesser critical peak kWp power, which means it has strong potential to obviate the need for heavy investments in electrical infrastructures, ultimately contributing to mitigating rapid electricity price rises.